The Influence of Leadership Style and Organizational Culture On BPJS Ketenagakerjaan Employee Performance Through Motivation Work - Muhammad Al Ghozali; Musran Munizu; Nurdjanah Hamid (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aimed to analyze the influence of leadership style and organizational culture on employee performance of BPJS Ketenagakerjaan work motivation as an intervening variable in the Sulawesi Maluku regional office and its branch offices.This performance is the achievement of the work results and work behavior of an employee by completing work assignments and achieving the criteria set by the company with the ability of the employee. The research method used a quantitative approach. The number sample was 204 people, namely BPJS employees of the Sulawesi, Maluku regional office and its branch offices. The data source used was primary data, namely the parties who become respondents. The results showed that leadership style and organizational culture had a positive and significant effect on motivation at the BPJS Ketenagakerjaan in the Sulawesi, Maluku region and its branch offices. Leadership style, organizational culture and motivation have a positive and significant effect on employee performance at the BPJS Ketenagakerjaan office in the Sulawesi, Maluku region and its branch offices. Leadership style and organizational culture have a positive and significant effect on employee performance through motivation at the BPJS Ketenagakerjaan office in the Sulawesi, Maluku region and its branch offices. Keywords: leadership style; organizational culture; motivation; performance